Saudi Women Participation in Sports Critical Analysis of Presupposition Strategies in Arabic Online News Discourse - Farah Nadia Harun; Muhammad Marwan Ismail (USIM Press, 2024)
Vol. 5 No. 2 (2020): Jurnal Sains Insani